GAMBARAN PENGARUH PELATIHAN DALAM PENINGKATAN PENGETAHUAN PEER GRUP KADER REMAJA KESEHATAN TENTANG PENYAKIT TUBERCOLOSIS DI SEKOLAH MENENGAH PERTAMA KECAMATAN CAKUNG JAKARTA TIMUR - Nuraini, Novia (Jurnal Penelitian Keperawatan Medik, 2023)
Tuberculosis sufferers in Indonesia were the 2nd highest in 2018 at 566,623 cases. In 2019, there were 543,874 cases of tuberculosis. The highest number of cases was reported from provinces with large populations, namely West Java, East Java and Central Java (Ministry of Health, 2019). One way to reduce the rate of TB disease is by forming special health cadres for TB. Ridwan et al, 2016 in their research on adolescent health cadres caring for TB, stated that after carrying out 5 on the job training, adolescent cadres were able to provide information about adolescent health to all students in the class. each. The aim of the research was to describe the influence of training in increasing the knowledge of peer groups of teenagers about tuberculosis in junior high schools. Method: A qualitative approach that included in-depth interviews, groups discussion, and observations in peer groups of adolescent in junior high schools. The analysis used is thematic. Research results: there was an increase in adolescent knowledge after training on tuberculosis transmission, prevention and treatment in families and the community around adolescent. Conclusion: It is hoped that the results of this research will continue to utilize health worker cadres from schools, health centers, and sub-district and sub-district government agencies.